PURWARUPA PENGATURAN KECEPATAN GENERATOR DC PEMBANGKIT LISTRIK PICOHYDRO BERBASIS PID - Dwi Aryadi Sudibya Sihombing; Widyono Hadi; Bambang Sri Kaloko (Jurnal Arus Elektro Indonesia, 2020)
The study used PID to control the direction of dc motor spin on faucets to regulate water. No controller has oscillations, because the system is nonlinear. Controlled by functionality is the best way for nonlinear systems. PID is the best choice for achieving tasks. Kp 20 Ki 10 and Kd 1. When the voltage is less than 12V, pid responds to increase voltage, logic on relay chanel one is 0 and 1 on relay chanel two. Chanel one relay NC, relay chanel two NC to NO so the motor rotates to the left up to voltage 12V then PID stops. When the voltage is more than 12V, pid responds to lower the voltage. logic relay chanel one is 1 and 0 on the relay chanel two. Relay chanel one NC becomes NO, relay chanel two NC, so the motor rotates to the right. PID response is inversely proportional to voltage.